ANALISIS PENGARUH PERSEPSI WP UMKM YANG TERDAMPAK COVID 19 TERHADAP PENETAPAN KEBIJAKAN PPH FINAL SESUAI PP NO 23 TAHUN 2018 - Rai Gina Artaningrum; Luh Diah Citraresmi Cahyadi; Amrulloh Amrulloh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of the perception of MSME taxpayers who are affected by Covid 19 on the determination of the final income tax policy according to Government Regulation PP number 23 of 2018. This type of research is descriptive which describes the perception of taxpayers to Government Regulation Number 23 of 2018. Samples from This study consisted of 97 respondents with convenience sampling technique. The data analysis technique used validity test, reliability test and multiple linear regression analysis. The results of the study stated that tax socialization, ease of taxation and tax sanctions had a positive effect on the determination of final income tax policy according to government regulation PP number 23 of 2018. The variable of tax socialization must be carried out regularly because the regulations and socialization of taxation held must be able to convey all information into Taxpayers, the tax convenience variable can be seen that regulated in PP No. 23 of 2018 has decreased rates then the tax sanctions are getting better or the tax sanctions are stricter, the taxpayers will fulfill their tax obligations if they view that tax sanctions will harm the taxpayer more.